SELF-RESTORATION OF SOILS IN ZONES OF TECHNOGENIC IMPACT OF METALLURGY BY MEANS OF SOIL MICROORGANISMS (Eurasian Journal of Ecology, 2026)
The East Kazakhstan region, including the city of Oskemen, is one of the main regions of the country for the extraction of non-ferrous metals. The impact of heavy metals during the operation of industrial facilities and their free storage lead to the spread of pollutants. Thus, an increase in the content of trace elements (Zn, Cu) and the accumulation of heavy metals (Pb, Cd) affects the entire soil ecosystem. Soil is an environment capable of self-regulation, in which, during the life of microorganisms, heavy metals are converted into forms bioavailable for phytoremediation.This article is aimed at correlating previously studied microorganisms with high tolerance to heavy metals with local microorganisms in order to describe the reaction characteristics of strains of local microorganisms.The selected bacteria and fungi showed a less stable reaction to high concentrations of heavy metals due to the poverty of the soil. The most viable microorganism was the bacterium Klebsiella sp. It was detected with a frequency of 64%. In light loamy soils, microorganisms showed higher survival rates with significant concentrations of heavy metals.Keywords: heavy metals, soil, microorganisms, PCR, remediation, bacteria, fungi.